THE EFFECT OF USING MUSIC VIDEOON THESTUDENTS’ ACHIEVEMENTIN WRITING NARRATIVE TEXT - Ayu Widyaningtyas and Sri Minda Murni (REGISTER: Journal of English Language Teaching of FBS-Unimed, 2015)
This study is aimed at investigating the effect of Music Video on the students’ achievement in writing narrative text. The objective was to find outthe effect of Music video to improve students’ achievement in writing narrative text. This study was conducted by experimental research. The population of this study was the eleventh grade students’ of SMA Negeri7 Medan. Two classes from ten parallel classes was taken for the observation by cluster random sampling which divided into two groups, each group consisted of 35 students as control group and experimental group. The experimental group was taught by using Music Video meanwhile the control group was taught by lecturing method. The instrument for collecting data was writing test. In the calculation of Ttest, the mean of students’ score in experimental group was 7,02 and the mean of students’ score in control group was 3,22. Standard deviation of experimental group was 516,974, standard deviation of control group 242,174, and the total number of samples was 68, Tobserved is higher than Ttable. 5,093 > 1,994 at the level of significance 0,05 for two tailed. The finding is if hypothesis stated that there is significant effect of using Music Video as media learning on students’ writing achievement on writing Narrative text is accepted.